Effects of personal and task constraints on limb coordination during walking: A systematic review and meta-analysis. (January 2019) - Shafizadeh, Mohsen; Crowther, Robert; Wheat, Jonathan; Davids, Keith
Abstract: Background: In human behaviour, emergence of movement patterns is shaped by different, interacting constraints and consequently, individuals with motor disorders usually display distinctive lower limb coordination modes. Objectives: To review existing evidence on the effects of motor disorders and different task constraints on emergent coordination patterns during walking, and to examine the clinical significance of task constraints on gait coordination in people with motor disorders. Methods: The search included CINHAL Plus, MEDLINE, HSNAE, SPORTDiscus, Scopus, Pubmed and AMED. We included studies that compared intra-limb and inter-limb coordination during gait between individuals with a motor disorder and able-bodied individuals, and under different task constraints. Two reviewers independently examined the quality of studies by using the Newcastle Ottawa Scale-cohort study. Findings: From the search results, we identified 1416 articles that studied gait patterns and further analysis resulted in 33 articles for systematic review and 18 articles for meta-analysis-1, and 10 articles for meta-analysis-2. In total, the gait patterns of 539 patients and 358 able-bodied participants were analysed in the sampled studies. Results of the meta-analysis for group comparisons revealed a low effect size for group differences (ES = −0.24), and a moderate effect size for task interventions (ES = −0.53), on limb coordination during gait. Interpretation: Findings demonstrated that motor disorders can be considered as an individual constraint, significantly altering gait patterns. These findings suggest that gait should be interpreted as functional adaptation to changing personal constraints, rather than as an abnormality. Results imply that designing gait interventions, through modifying locomotion tasks, can facilitate the emergent re-organisation of inter-limb coordination patterns during rehabilitation. Highlights: This study reviewed studies on movement coordination during walking. Participants were from people with motor disabilities and able-bodied people. Most studies have used continuous relative phase as an index of coordination during walking. Able-bodied utilised joint coordination different than patients. Some interventions have direct effect on coordination adaptation in people with motor disability.